Between Dissent and Power The Transformation of Islamic Politics in the Middle East and Asia - Teik, Khoo Boo.; Hadiz, Vedi R.; Nakanishi, Yoshihiro. (IDE-JETRO Series, 2014)
This study examines the collective progression of Islamic politics between points of dissent and positions of power. It brings about a more a serious understanding of Islamic politics by critically tracing the pathways by which Islamic politics has been transformed in the Middle East and Asia.